Tatbiq Thariqah at-Tafkir wa al-Iqtiran wa al-Musyarakah fi Tarqiyah Nataij Maharah al-Kitabah li Thullab as-Shaf as-Tsamin fi Ma'had al-Islami Insan Mulia Punggur - Siti Hamidah; Nailul Izzah; Kholida Nur (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2026)
This study aims to examine the impact of the Think Pair Share (TPS) method on improving the writing skills (maharoh kitabah) of eighth-grade students at Ponpes Insan Mulia Punggur. The research background highlights challenges faced by students, such as low interest and active participation in learning writing skills. Using a quantitative experimental approach, 28 students were divided into an experimental class (using TPS) and a control class (without TPS). Data collection involved pretests, posttests, observations, and interviews. Results showed a significant improvement in the experimental class compared to the control class. In the experimental group, the average pretest score was 65.3 (57% mastery), increasing to 79.29 (93% mastery) in the posttest. Meanwhile, the control group’s average pretest score was 52.5 (14% mastery), rising to 61.42 (36% mastery) in the posttest. This aligns with previous studies demonstrating TPS's effectiveness in enhancing student learning outcomes